Adenosine A2b receptors control A1 receptor‐mediated inhibition of synaptic transmission in the mouse hippocampus. (19th February 2015) - Gonçalves, Francisco Q.; Pires, Johny; Pliassova, Anna; Beleza, Rui; Lemos, Cristina; Marques, Joana M.; Rodrigues, Ricardo J.; Canas, Paula M.; Köfalvi, Attila; Cunha, Rodrigo A.; Rial, Daniel
Abstract Adenosine is a neuromodulator mostly acting through A1 (inhibitory) and A2A (excitatory) receptors in the brain. A2B receptors (A2BR) are Gs/q‐protein‐coupled receptors with low expression in the brain. As A2BR function is largely unknown, we have now explored their role in the mouse hippocampus. We performed electrophysiological extracellular recordings in mouse hippocampal slices, and immunological analysis of nerve terminals and glutamate release in hippocampal slices and synaptosomes. Additionally, A2BR‐knockout (A2BR‐KO) and C57/BL6 mice were submitted to a behavioural test battery (open field, elevated plus‐maze, Y‐maze). The A2BR agonist BAY60‐6583 (300 nm) decreased the paired‐pulse stimulation ratio, an effect prevented by the A2BR antagonist MRS 1754 (200 nM) and abrogated in A2BR‐KO mice. Accordingly, A2BR immunoreactivity was present in 73 ± 5% of glutamatergic nerve terminals, i.e. those immunopositive for vesicular glutamate transporters. Furthermore, BAY 60‐6583 attenuated the A1R control of synaptic transmission, both the A1R inhibition caused by 2‐chloroadenosine (0.1–1 μm) and the disinhibition caused by the A1R antagonist DPCPX (100 nm), both effects prevented by MRS 1754 and abrogated in A2BR‐KO mice. BAY 60‐6583 decreased glutamate release in slices and also attenuated the A1R inhibition (CPA 100 nm). A2BR‐KO mice displayed a modified exploratory behaviour with an increased time in the central areas of the open field, elevated plus‐maze and the Y‐maze and no alteration of locomotion, anxiety or working memory. We conclude that A2BR are present in hippocampal glutamatergic terminals where they counteract the predominant A1R‐mediated inhibition of synaptic transmission, impacting on exploratory behaviour.